"Nothing Happened Without Music": Teaching and Learning the Anatolian Bağlama in Berlin. (November 2019) - O'TOOLE, MICHAEL
Abstract : In his article "The Ethnomusicology of Music Learning and Teaching, " Timothy Rice argues that the practices of teaching and learning music are fundamental to the ways in which music is conceptualised, transmitted, and invested with symbolic meanings (2003). Ethnomusicologists studying music and diaspora have also drawn attention to the significance of music education as a key medium for the construction and maintenance of diasporic identities. 1 In diasporic communities, music education can be a principal means for transmitting perspectives on the historical and political forces that have shaped the diaspora and for developing the linguistic and cultural competency of younger generations. Music schools and other institutions of musical learning can also play important roles in the public representation of diasporic communities and in articulating the relationship of the diaspora to the linguistic, musical, religious, and national heritage of its perceived homeland.